Product evaluation and purchase intention : impact of country-of-origin and experience in living in a foreign country - Wong, Chui Yim; Garma, Romana; Polonsky, Michael Jay (Sunway University College, 2007)
This article presents the results of an experiment that compares the perceptions of product quality and purchase intentions of foreign versus home products by Chinese consumers who have had experience living in a western society compared to those living in China. The results indicate experience does affect purchase likelihood for home versus foreign products. Chinese, generally, find country of parts as the best cue in evaluating product quality and purchase intentions.